A multifunctionalization of octafluorocyclopentene under mild conditions. (April 2018) - Krishnan, Ranganathan; Parthiban, Anbanandam
Graphical abstract: A series of 1, 5- and 1, 5-phenoxy capped 2, 4-linear polymers were synthesized by reacting octafluorocyclopentene (OFCP) and bisphenols at room temperature and above. The 1, 5-linear polymers were post functionalized using different phenols, whereas the 2, 4-linear polymers were synthesized from 1, 5-phenoxy substituted OFCP compounds and bisphenols. The pre and post functionalization of 2, 4- and 1, 5-linear polymers were confirmed by MALDI-TOF MS analysis. The above analysis proves that OFCP possesses two set of four reactive fluorine atoms (4F) at 1, 5- (2F) and 2, 4-positions (2F) undergoes stepwise nucleophilic substitution reactions. Highlights: A multifunctionalization are carried out using non-aromatic cyclic compound at RT. Linear polymers from (1, 5) and (2, 4) two different positions of Octafluorocyclopentene molecule. Diversified functional groups attached on linear polymers by pre and post modifications. Structural characterized using MALDI-TOF MS spectrum to evaluate the compositions of the polymer chains. Abstract: Octafluorocyclopentene (OFCP) undergoes multiple substitutions with nucleophiles derived from phenols in a stepwise manner. The vinylic fluorine atoms at 1 and 5-positions undergoes displacement exclusively in the first step followed by the displacement of two fluorine atoms, one each at 2 and 4-positions and no further substitution occurs beyond the tetrasubstitution. Two types of semi-fluorinated linear polymers bearing various pendant groups were synthesized. In the first type, the polymer chain was formed by substitution at 1 and 5-positions with bisphenols and pendant groups at 2 and 4-positions. In the second type, the pendant groups were introduced at 1 and 5-positions first followed by the nucleophilic substitutions at 2 and 4-positions with bisphenols. Azo group (NN) was one of the functional moieties introduced among the various pendant groups. Both small organic compounds as well as polymers were thoroughly characterized by various analytical techniques including 19 F NMR spectroscopy, electrospray ionization time-of-flight mass analysis (ESI-TOF MS), matrix assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS), UV–Vis spectrophotometric analysis, etc. The stepwise, multiple substitution occurring in OFCP is highly useful for making semi-fluorinated functional organic compounds and polymers.